Partial characterization and tissue-specific expression profile of immunoglobulin M heavy chain gene in rohu, Labeo rohita (Hamilton, 1822) - SARAVANAN, K; RAJENDRAN, K V; CHAUDHARI, APARNA; PURUSHOTHAMAN, C S; MUKESH, M (The Indian Journal of Animal Sciences, 2013)
The present study was aimed to characterize the immunoglobulin M (IgM) heavy chain gene in rohu, Labeo rohita, and its tissue-specific expression. A 451 bp segment of IgM heavy chain gene of rohu spanning the variable region was amplified and sequenced. The partial nucleotide sequence of the rohu IgM heavy chain gene showed 91, 90 and 87%homology with IgM of Cyprinus carpio, Danio rerio and Ctenopharyngodon idella respectively. The deduced aminoacid sequence of the partial rohu IgM heavy chain gene was 85, 82 and 79% identical to that of C. carpio, C. idella and D. rerio, respectively. Quantitative real-time PCR analysis of the IgM heavy chain gene expression in various tissuesrevealed that the highest expression was in the lymphoid tissues, namely kidney and spleen followed by heart,Â  intestine, gill, liver and muscle. It was also observed that the IgM heavy chain gene expression increased with age, i.e. 6-monthold fish showed higher levels than 4-month-old and 2-month-old fishes.